Generalized Quasilinearization Using Coupled Lower and Upper Solutions for Periodic Boundary Value Problem of an Integro Differential Equation (European Journal of Pure and Applied Mathematics, 2019)
In this paper we rst develop the method of generalized quasilinearization for initialvalue problem of an integro dierential equation and then use it to develop quasilinearization forÂ the periodic boundary value problem of the integro dierential equation by using the coupled lowerÂ and upper solutions of Type-I.